Preparation method and application of polyethylene strong cross film
By introducing modified ethylene-vinyl acetate copolymer and adamantane into the polyethylene strong cross film, the problems of poor heat resistance, flammability and low mechanical strength of the polyethylene strong cross film are solved, and the heat resistance and flame retardant properties of the polyethylene strong cross film are significantly improved.
Patent Information
- Application Number
- CN202411859457.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-25
AI Technical Summary
The existing polyethylene strong cross film has problems such as poor heat resistance, flammability and low mechanical strength, which limits its application in high temperature environments.
By introducing modified ethylene-vinyl acetate copolymer and adamantane into the polyethylene strong cross film, a polyethylene strong cross film has been prepared through multi-layer coextrusion blow molding and cross-composite technology.
The heat resistance and flame retardant properties of the polyethylene strong cross film are significantly improved, so that it can exhibit relatively stable mechanical properties and flame retardant properties in high temperature environments.
Smart Images

Figure BDA0005192819320000051 
Figure BDA0005192819320000061 
Figure BDA0005192819320000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer film processing, in particular to a preparation method and application of a polyethylene strong cross film. Background Art
[0002] Polyethylene strong cross film is a high-strength multi-layer composite film. It is made of polyethylene as the base material, and is added with masterbatch and related additives. It is blown into embryos through multi-layer co-extrusion, multi-fold stretching, and rotary cutting into sheet film substrates with a horizontal and vertical distribution of 45°, and finally completed through cross-compounding. Compared with ordinary blown film products, polyethylene strong cross film has higher strength, toughness, tear resistance and dimensional stability, and is used in waterproof membranes, label films, heavy packaging and other fields; especially plays an important role in the waterproofing of building materials, such as basements, subways, tunnels, pools, roof gardens and other engineering waterproofing and non-exposed layers, underground waterproofing projects and other fields. However, since the strong cross film itself is not heat-resistant, when used in roof waterproofing projects, a certain thickness of concrete protective layer is required on the surface, which not only increases the load on the roof, but also ordinary strong cross film is a combustible material, which is very easy to ignite when encountering open flames, posing a great safety hazard; therefore, the modification of polyethylene strong cross film has become the focus of current research.
[0003] At present, domestic polyethylene strong cross membranes are mainly used in wet-laid waterproof membranes and other polymer membranes for waterproofing applications; the existing polyethylene strong cross membranes have poor heat resistance and low bonding strength between composite layers and between composite layers and other functional layers, which limits their application. For example, when the polyethylene strong cross membrane waterproof membrane is laid at high temperature, it is prone to warping, wrinkling and even burning due to the poor heat resistance and flame retardancy of the polyethylene strong cross membrane; Patent No. CN109294469B discloses an exposed flame-retardant strong cross membrane self-adhesive waterproof membrane and a preparation method, including a surface anti-aging layer, a flame-retardant strong cross membrane waterproof layer and a self-adhesive adhesive layer. Compared with the existing strong cross membrane self-adhesive waterproof membrane, it has a longer service life, better waterproof and flame retardant properties, and is particularly suitable for roof waterproofing projects, but has poor high temperature resistance and relatively low bonding strength, and is limited in use in the field of waterproof membranes. Patent No. CN113621196B discloses a polyethylene strong cross film, a preparation method thereof, and an application thereof. The film is formed by cross-compounding multiple layers of films, each layer of the film includes a high-density polyethylene blend, a modified resin and poly-4-methyl-1-pentene, and has excellent heat resistance and low-temperature flexibility. However, the prepared strong cross film has insufficient toughness and the flame retardant properties of the strong cross film have not been effectively improved.
[0004] In summary, the current polyethylene strong cross membrane still has disadvantages such as low mechanical properties, poor heat resistance, and easy burning. Therefore, the development of a new high-performance polyethylene strong cross membrane is of great significance to broadening the application field of polyethylene cross membrane. Summary of the invention
[0005] The purpose of the present invention is to solve the problems existing in the above-mentioned prior art and to provide a preparation method and application of a polyethylene strong cross film, aiming to solve the problems of poor heat resistance, easy flammability and low mechanical strength of the existing strong cross film.
[0006] The present invention is achieved through the following technical solutions:
[0007] A method for preparing a polyethylene strong cross film is carried out according to the following steps:
[0008] Step (1), under a nitrogen atmosphere, add deionized water and polyvinyl alcohol to a reaction flask equipped with a thermometer and a reflux condenser, heat to 85-100° C., stir and dissolve, cool to 35-45° C., add ethylene, vinyl acetate, maleic anhydride, alkenyl nitrogen phosphorus silicon adamantane monomer and ammonium persulfate, react at 80-90° C. for 2-4 hours, cool to below 50° C., add dibutyl phthalate, stir evenly, adjust the pH to 5-6, and cool to obtain a modified ethylene-vinyl acetate copolymer.
[0009] Step (2), after uniformly mixing 70-85 parts of high-density polyethylene, 20-35 parts of linear low-density polyethylene and 8-15 parts of metallocene polyethylene by weight, blow-molding the mixture into a film through a multi-layer co-extrusion blown film machine, and subjecting the obtained film to constant temperature stretching and 45° rotary cutting to obtain a raw film; preparing an intermediate layer modified film by the same process from 50-65 parts of high-density polyethylene, 10-25 parts of linear low-density polyethylene, 5-25 parts of modified ethylene-vinyl acetate copolymer and 10-20 parts of mica masterbatch; placing the intermediate layer modified film between two layers of raw film, bonding them with a polyurethane adhesive, winding and aging, and obtaining a polyethylene strong cross film.
[0010] Furthermore, in step (1), the mass ratio of polyvinyl alcohol, ethylene, vinyl acetate, maleic anhydride, alkenyl nitrogen phosphorus silicon adamantane monomer, ammonium persulfate, and dibutyl phthalate is 10-15:100:35-50:10-20:1-5:3-8:0.5-1.
[0011] Furthermore, in step (2), the die head temperature of the multilayer co-extrusion blown film machine is 180-220° C., the wind pressure is 5-10 MPa, and the main engine frequency is 30-50 Hz.
[0012] Furthermore, the preparation method of the alkenyl nitrogen phosphorus silicon adamantane monomer in step (1) is carried out according to the following steps:
[0013] Step S1, under a nitrogen atmosphere, add 4-methoxyphenylphosphonic dichloride and acetonitrile to a reaction flask equipped with a thermometer, stir evenly, then add adamantane and triethylamine, stir to react, after the reaction is completed, concentrate under reduced pressure, purify by column chromatography (elution with dichloromethane / methanol = 20:1), and dry to obtain phosphanidoadamantane methoxybenzene.
[0014] Step S2, under a nitrogen atmosphere, add phosphanidoadamantane methoxybenzene and dichloromethane to a reaction flask equipped with a thermometer, stir evenly, add boron tribromide dropwise under ice bath conditions, react at 0-10° C. for 12-24 h, extract with ethyl acetate and deionized water, concentrate the organic phase, and dry to obtain phosphanidoadamantane phenol.
[0015] Step S3, under a nitrogen atmosphere, add phosphanidoadamantyl phenol and N,N-dimethylformamide to a reaction flask equipped with a thermometer, stir evenly, add chlorotrivinylsilane and pyridine, stir to react, and after the reaction is completed, concentrate under reduced pressure, purify by column chromatography (elution with n-heptane / ethyl acetate = 3:1), and dry to obtain an alkenyl nitrogen phosphanidoadamantane monomer.
[0016] Furthermore, in step S1, the molar ratio of 4-methoxyphenylphosphonic dichloride, adamantane amine and triethylamine is 1:2.05-2.2:1.5-1.8.
[0017] Furthermore, in step S1, the reaction temperature is 60-75° C., and the reaction time is 5-10 h.
[0018] Furthermore, in step S2, the molar ratio of phosphanitrogen adamantane methoxybenzene to boron tribromide is 1:1.2-1.5.
[0019] Furthermore, in step S3, the molar ratio of phosphanitrogen adamantyl phenol, chlorotrivinylsilane and pyridine is 1:1.1-1.3:0.9-1.05.
[0020] Furthermore, in step S3, the reaction temperature is 70-90° C., and the reaction time is 8-16 h.
[0021] Furthermore, the polyethylene strong cross membrane is used in waterproof building materials.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] The invention uses 4-methoxyphenylphosphonyl dichloride, adamantane amine and chlorotrivinylsilane as raw materials, obtains alkenyl nitrogen phosphorus silicon adamantane monomer through chemical reaction, and grafts and polymerizes with ethylene, vinyl acetate, maleic anhydride and the like to obtain modified ethylene-vinyl acetate copolymer. Finally, raw film made of high-density polyethylene, linear low-density polyethylene and the like; intermediate layer modified film made of modified ethylene-vinyl acetate copolymer, mica masterbatch and the like are cross-compounded to obtain polyethylene strong cross film.
[0024] The modified ethylene-vinyl acetate copolymer is similar to the polyethylene matrix in structure and has good compatibility. Maleic anhydride can produce a bonding reaction with the hydroxyl groups on the surface of the mica masterbatch to form a cross-linked region similar to an interpenetrating network structure, so that the mica masterbatch is evenly dispersed in the matrix, significantly improving the mechanical properties of the cross-membrane; the cyclic structure of adamantane has a certain rigidity, so that the molecule can better transmit and disperse stress when subjected to force, reduce local stress concentration, and improve the tensile strength of the material; when subjected to high temperature, the silicone in the modified ethylene-vinyl acetate copolymer will form a dense SiO2 protective layer on the surface, which can effectively prevent external air from diffusing inward. Combined with the rigid heat-resistant structure of adamantane, the membrane material exhibits a more stable characteristic under high temperature conditions.
[0025] The nitrogen, phosphorus and silicon in the modified ethylene-vinyl acetate copolymer produce a synergistic flame retardant effect, wherein the phosphorus element and the silicon element can promote the formation of the carbon layer, absorb a large amount of heat during the decomposition process, reduce the temperature of the burning polymer, and inhibit the combustion; the non-combustible gas produced by the decomposition of the nitrogen element can dilute the combustible gas, further improving the stability and density of the carbon layer. The synergistic effect of the three enables the cross film to form a more solid carbon layer at high temperature, more effectively isolate oxygen and heat, and thus improve the flame retardant properties of the polyethylene strong cross film. The polyethylene cross film prepared by the present invention has high peeling strength and good low-temperature flexibility, and has a wide range of applications. DETAILED DESCRIPTION
[0026] The technical scheme in the embodiment of the present invention is specifically and detailedly described below. It should be noted that for those of ordinary skill in the art, without departing from the principle of the present invention, some modifications and improvements can also be made, which should also be considered to belong to the protection scope of the present invention. Unless otherwise specified, the raw materials and reagents used in this application are all commercially available products, or can be prepared by known methods.
[0027] High-density polyethylene: Model 6888, purchased from Sinopec Daqing Refining and Chemical Company.
[0028] Linear low-density polyethylene: Model 7042, purchased from Ningxia Baofeng Energy Group Co., Ltd.
[0029] Mica masterbatch: particle size is 1200 mesh, purchased from Shijiazhuang Chilin Mineral Products Co., Ltd.
[0030] Polyurethane adhesive: Model: XH50E, purchased from Guangdong Xinhui Chemical Co., Ltd.
[0031] 4-Methoxyphenylphosphonic acid dichloride, CAS number is 37632-18-1.
[0032] Amantadine, CAS number is 768-94-5.
[0033] Chlorotrivinylsilane, CAS number is 1871-21-2.
[0034] Example 1
[0035] (1) Under a nitrogen atmosphere, 85 mmol of 4-methoxyphenylphosphonic acid dichloride and 340 mL of acetonitrile were added to a reaction flask equipped with a thermometer. After stirring, 180.2 mmol of adamantane amine and 136 mmol of triethylamine were added, and the mixture was reacted at 65° C. for 8 h. The mixture was concentrated under reduced pressure and purified by column chromatography (elution with dichloromethane / methanol = 20:1). After drying, adamantane methoxybenzene was obtained.
[0036] (2) In a nitrogen atmosphere, 80 mmol of phosphanidoadamantane methoxybenzene and 680 mL of dichloromethane were added to a reaction flask equipped with a thermometer. After stirring evenly, 108 mmol of boron tribromide was added dropwise under ice bath conditions. The mixture was reacted at 5° C. for 16 h, extracted with ethyl acetate and deionized water, and the organic phase was concentrated and dried to obtain phosphanidoadamantane phenol. The preparation reaction formula is as follows:
[0037]
[0038] (3) Under nitrogen atmosphere, add 72 mmol of phosphanidoadamantylphenol and 970 mL of N,N-dimethylformamide to a reaction flask equipped with a thermometer, stir evenly, add 90 mmol of chlorotrivinylsilane and 72 mmol of pyridine, react at 80° C. for 12 h, concentrate under reduced pressure, purify by column chromatography (elution with n-heptane / ethyl acetate = 3:1), and dry to obtain an olefinic nitrogen phosphanidoadamantane monomer. The preparation reaction formula is as follows:
[0039]
[0040] (4) Under a nitrogen atmosphere, 35 g of deionized water and 12 g of polyvinyl alcohol were added to a reaction flask equipped with a thermometer and a reflux condenser, the temperature was raised to 95° C. and stirred to dissolve, the temperature was lowered to 40° C., 100 g of ethylene, 40 g of vinyl acetate, 15 g of maleic anhydride, 1 g of alkenyl nitrogen phosphorus silicon adamantane monomer and 5 g of ammonium persulfate were added, the mixture was reacted at 85° C. for 3 h, the temperature was lowered to below 50° C., 0.6 g of dibutyl phthalate was added, the mixture was stirred evenly, the pH was adjusted to 5, and the modified ethylene-vinyl acetate copolymer was obtained after cooling.
[0041] (5) After 75 g of high-density polyethylene, 25 g of linear low-density polyethylene and 12 g of metallocene polyethylene are uniformly mixed, the film is blown into a film by a multi-layer co-extrusion blow molding machine, the die temperature is 200 ° C, the wind pressure is 8 MPa, the main machine frequency is 40 Hz, and the obtained film is subjected to constant temperature stretching and 45° rotary cutting to obtain a raw film; 55 g of high-density polyethylene, 20 g of linear low-density polyethylene, 5 g of modified ethylene-vinyl acetate copolymer and 10 g of mica masterbatch are prepared according to the same process to obtain an intermediate layer modified film; the intermediate layer modified film is placed between two layers of raw film and bonded with a polyurethane adhesive with a coating amount of 2 g / m 2 , winding and aging to obtain a polyethylene strong cross film.
[0042] Example 2
[0043] (1) Under a nitrogen atmosphere, 150 mmol of 4-methoxyphenylphosphonic acid dichloride and 450 mL of acetonitrile were added to a reaction flask equipped with a thermometer. After stirring, 307.5 mmol of adamantane amine and 225 mmol of triethylamine were added. The mixture was reacted at 75° C. for 5 h, concentrated under reduced pressure, purified by column chromatography (eluted with dichloromethane / methanol = 20:1), and dried to obtain phosphanidoadamantane methoxybenzene.
[0044] (2) Under a nitrogen atmosphere, 135 mmol of phosphanidoadamantane methoxybenzene and 810 mL of dichloromethane were added to a reaction flask equipped with a thermometer. After stirring, 162 mmol of boron tribromide was added dropwise in an ice bath. The mixture was reacted at 10° C. for 12 h, extracted with ethyl acetate and deionized water, and the organic phase was concentrated and dried to obtain phosphanidoadamantane phenol.
[0045] (3) Under a nitrogen atmosphere, 120 mmol of phosphanidoadamantyl phenol and 1440 mL of N,N-dimethylformamide were added to a reaction flask equipped with a thermometer. After stirring, 132 mmol of chlorotrivinylsilane and 108 mmol of pyridine were added, and the mixture was reacted at 90° C. for 8 h. The mixture was concentrated under reduced pressure and purified by column chromatography (elution with n-heptane / ethyl acetate = 3:1). After drying, an alkenyl nitrogen phosphorus silicon adamantane monomer was obtained.
[0046] (4) Under a nitrogen atmosphere, 35 g of deionized water and 10 g of polyvinyl alcohol were added to a reaction flask equipped with a thermometer and a reflux condenser, the temperature was raised to 100° C. and stirred to dissolve, the temperature was lowered to 45° C., 100 g of ethylene, 50 g of vinyl acetate, 20 g of maleic anhydride, 2 g of alkenyl nitrogen phosphorus silicon adamantane monomer and 3 g of ammonium persulfate were added, the reaction was carried out at 90° C. for 2 h, the temperature was lowered to below 50° C., 1 g of dibutyl phthalate was added, the mixture was stirred evenly, the pH was adjusted to 6, and the modified ethylene-vinyl acetate copolymer was obtained after cooling.
[0047] (5) After 70 g of high-density polyethylene, 30 g of linear low-density polyethylene and 8 g of metallocene polyethylene are uniformly mixed, the film is blown into a film by a multi-layer co-extrusion blown film machine, the die temperature is 220°C, the wind pressure is 10 MPa, the main machine frequency is 50 Hz, and the obtained film is subjected to constant temperature stretching and 45° rotary cutting to obtain a raw film; 50 g of high-density polyethylene, 25 g of linear low-density polyethylene, 10 g of modified ethylene-vinyl acetate copolymer and 12 g of mica masterbatch are prepared according to the same process to obtain an intermediate layer modified film; the intermediate layer modified film is placed between two layers of raw film and bonded with a polyurethane adhesive with a coating amount of 2 g / m 2 , winding and aging to obtain a polyethylene strong cross film.
[0048] Example 3
[0049] (1) Under a nitrogen atmosphere, 40 mmol of 4-methoxyphenylphosphonic acid dichloride and 200 mL of acetonitrile were added to a reaction flask equipped with a thermometer. After stirring, 88 mmol of adamantane amine and 72 mmol of triethylamine were added. The mixture was reacted at 60° C. for 10 h, concentrated under reduced pressure, purified by column chromatography (eluted with dichloromethane / methanol = 20:1), and dried to obtain phosphanidoadamantane methoxybenzene.
[0050] (2) Under a nitrogen atmosphere, 35 mmol of phosphanidoadamantane methoxybenzene and 350 mL of dichloromethane were added to a reaction flask equipped with a thermometer. After stirring, 52.5 mmol of boron tribromide was added dropwise in an ice bath. The mixture was reacted at 0°C for 24 h, extracted with ethyl acetate and deionized water, and the organic phase was concentrated and dried to obtain phosphanidoadamantane phenol.
[0051] (3) Under a nitrogen atmosphere, 28 mmol of phosphanidoadamantylphenol and 420 mL of N,N-dimethylformamide were added to a reaction flask equipped with a thermometer. After stirring, 36.4 mmol of chlorotrivinylsilane and 29.4 mmol of pyridine were added, and the mixture was reacted at 70° C. for 16 h. The mixture was concentrated under reduced pressure, purified by column chromatography (eluted with n-heptane / ethyl acetate = 3:1), and dried to obtain an olefinic nitrogen phosphanidoadamantane monomer.
[0052] (4) Under a nitrogen atmosphere, 35 g of deionized water and 15 g of polyvinyl alcohol were added to a reaction flask equipped with a thermometer and a reflux condenser, the temperature was raised to 85° C. and stirred to dissolve, the temperature was lowered to 35° C., 100 g of ethylene, 35 g of vinyl acetate, 20 g of maleic anhydride, 3 g of alkenyl nitrogen phosphorus silicon adamantane monomer and 3 g of ammonium persulfate were added, the mixture was reacted at 80° C. for 4 h, the temperature was lowered to below 50° C., 0.5 g of dibutyl phthalate was added, the mixture was stirred evenly, the pH was adjusted to 5, and the modified ethylene-vinyl acetate copolymer was obtained after cooling.
[0053] (5) 85 g of high-density polyethylene, 20 g of linear low-density polyethylene and 5 g of metallocene polyethylene were mixed evenly and blown into film by a multi-layer co-extrusion blown film machine. The die temperature was 180°C, the wind pressure was 5 MPa, and the main machine frequency was 50 Hz. The obtained film was subjected to constant temperature stretching and 45° rotary cutting to obtain a raw film; 65 g of high-density polyethylene, 10 g of linear low-density polyethylene, 15 g of modified ethylene-vinyl acetate copolymer and 15 g of mica masterbatch were prepared according to the same process to obtain an intermediate layer modified film; the intermediate layer modified film was placed between two layers of raw film and bonded with a polyurethane adhesive with a coating amount of 2 g / m 2 , winding and aging to obtain a polyethylene strong cross film.
[0054] Example 4
[0055] (1) Under a nitrogen atmosphere, 60 mmol of 4-methoxyphenylphosphonic acid dichloride and 270 mL of acetonitrile were added to a reaction flask equipped with a thermometer. After stirring, 130 mmol of adamantane amine and 105 mmol of triethylamine were added. The mixture was reacted at 70° C. for 9 h, concentrated under reduced pressure, purified by column chromatography (eluted with dichloromethane / methanol = 20:1), and dried to obtain phosphanidoadamantane methoxybenzene.
[0056] (2) Under a nitrogen atmosphere, 50 mmol of phosphanidoadamantane methoxybenzene and 425 mL of dichloromethane were added to a reaction flask equipped with a thermometer. After stirring, 68 mmol of boron tribromide was added dropwise in an ice bath. The mixture was reacted at 5° C. for 20 h. The mixture was extracted with ethyl acetate and deionized water. The organic phase was concentrated and dried to obtain phosphanidoadamantane phenol.
[0057] (3) Under a nitrogen atmosphere, 45 mmol of phosphanidoadamantylphenol and 630 mL of N,N-dimethylformamide were added to a reaction flask equipped with a thermometer. After stirring, 52.2 mmol of chlorotrivinylsilane and 44.1 mmol of pyridine were added, and the mixture was reacted at 85° C. for 15 h. The mixture was concentrated under reduced pressure and purified by column chromatography (elution with n-heptane / ethyl acetate = 3:1). After drying, an alkenyl nitrogen phosphorus silicon adamantane monomer was obtained.
[0058] (4) Under a nitrogen atmosphere, 35 g of deionized water and 13 g of polyvinyl alcohol were added to a reaction flask equipped with a thermometer and a reflux condenser, the temperature was raised to 95° C. and stirred to dissolve, the temperature was lowered to 40° C., 100 g of ethylene, 45 g of vinyl acetate, 12 g of maleic anhydride, 4 g of alkenyl nitrogen phosphorus silicon adamantane monomer and 7 g of ammonium persulfate were added, the mixture was reacted at 85° C. for 4 h, the temperature was lowered to below 50° C., 0.9 g of dibutyl phthalate was added, the mixture was stirred evenly, the pH was adjusted to 6, and the modified ethylene-vinyl acetate copolymer was obtained after cooling.
[0059] (5) 80 g of high-density polyethylene, 25 g of linear low-density polyethylene and 10 g of metallocene polyethylene were mixed evenly and blown into film by a multi-layer co-extrusion blown film machine. The die temperature was 210°C, the wind pressure was 8 MPa, and the main machine frequency was 45 Hz. The obtained film was subjected to constant temperature stretching and 45° rotary cutting to obtain a raw film; 55 g of high-density polyethylene, 15 g of linear low-density polyethylene, 20 g of modified ethylene-vinyl acetate copolymer and 18 g of mica masterbatch were prepared according to the same process to obtain an intermediate layer modified film; the intermediate layer modified film was placed between two layers of raw film and bonded with a polyurethane adhesive with a coating amount of 2 g / m 2 , winding and aging to obtain a polyethylene strong cross film.
[0060] Example 5
[0061] (1) Under a nitrogen atmosphere, 25 mmol of 4-methoxyphenylphosphonic acid dichloride and 90 mL of acetonitrile were added to a reaction flask equipped with a thermometer. After stirring, 55 mmol of adamantane amine and 42 mmol of triethylamine were added. The mixture was reacted at 70° C. for 10 h, concentrated under reduced pressure, purified by column chromatography (eluted with dichloromethane / methanol = 20:1), and dried to obtain phosphanidoadamantane methoxybenzene.
[0062] (2) Under a nitrogen atmosphere, 20 mmol of phosphanidoadamantane methoxybenzene and 170 mL of dichloromethane were added to a reaction flask equipped with a thermometer. After stirring, 28 mmol of boron tribromide was added dropwise in an ice bath. The mixture was reacted at 0°C for 18 h, extracted with ethyl acetate and deionized water, and the organic phase was concentrated and dried to obtain phosphanidoadamantane phenol.
[0063] (3) Under a nitrogen atmosphere, 16 mmol of phosphanidoadamantylphenol and 210 mL of N,N-dimethylformamide were added to a reaction flask equipped with a thermometer. After stirring, 18.5 mmol of chlorotrivinylsilane and 15.2 mmol of pyridine were added, and the mixture was reacted at 90° C. for 15 h. The mixture was concentrated under reduced pressure and purified by column chromatography (elution with n-heptane / ethyl acetate = 3:1). After drying, an alkenyl nitrogen phosphorus silicon adamantane monomer was obtained.
[0064] (4) Under a nitrogen atmosphere, 35 g of deionized water and 12 g of polyvinyl alcohol were added to a reaction flask equipped with a thermometer and a reflux condenser, the temperature was raised to 90° C. and stirred to dissolve, the temperature was lowered to 40° C., 100 g of ethylene, 40 g of vinyl acetate, 16 g of maleic anhydride, 5 g of alkenyl nitrogen phosphorus silicon adamantane monomer and 8 g of ammonium persulfate were added, the mixture was reacted at 90° C. for 3 h, the temperature was lowered to below 50° C., 0.6 g of dibutyl phthalate was added, the mixture was stirred evenly, the pH was adjusted to 5, and the modified ethylene-vinyl acetate copolymer was obtained after cooling.
[0065] (5) After 75 g of high-density polyethylene, 30 g of linear low-density polyethylene and 10 g of metallocene polyethylene are uniformly mixed, the mixture is blown into a film by a multi-layer co-extrusion blown film machine, the die temperature is 205°C, the wind pressure is 7 MPa, the main machine frequency is 45 Hz, and the obtained film is subjected to constant temperature stretching and 45° rotary cutting to obtain a raw film; 60 g of high-density polyethylene, 20 g of linear low-density polyethylene, 25 g of modified ethylene-vinyl acetate copolymer and 20 g of mica masterbatch are prepared according to the same process to obtain an intermediate layer modified film; the intermediate layer modified film is placed between two layers of raw film and bonded with a polyurethane adhesive with a coating amount of 2 g / m 2 , winding and aging to obtain a polyethylene strong cross film.
[0066] Comparative Example 1
[0067] (1) In a nitrogen atmosphere, 85 mmol of 4-methoxyphenylphosphonic acid dichloride and 340 mL of acetonitrile were added to a reaction flask equipped with a thermometer. After stirring, 180.2 mmol of aniline (structural formula: 62-53-3) and 136 mmol of triethylamine, react at 65°C for 8 h, concentrate under reduced pressure, purify by column chromatography (eluted with dichloromethane / methanol=20:1), and dry to obtain phosphanitromethoxybenzene.
[0068] (2) Under a nitrogen atmosphere, 80 mmol of phosphanitromethoxybenzene and 680 mL of dichloromethane were added to a reaction flask equipped with a thermometer. After stirring, 108 mmol of boron tribromide was added dropwise in an ice bath. The mixture was reacted at 5°C for 16 h, extracted with ethyl acetate and deionized water, and the organic phase was concentrated and dried to obtain phosphanitrophenol.
[0069] (3) Under a nitrogen atmosphere, 72 mmol of phosphinophenol and 970 mL of N,N-dimethylformamide were added to a reaction flask equipped with a thermometer. After stirring, 90 mmol of chlorotrivinylsilane and 72 mmol of pyridine were added. The mixture was reacted at 80° C. for 12 h, concentrated under reduced pressure, purified by column chromatography (eluted with n-heptane / ethyl acetate = 3:1), and dried to obtain an olefinic nitrogen phosphorus silicon monomer.
[0070] (4) Under a nitrogen atmosphere, 35 g of deionized water and 12 g of polyvinyl alcohol were added to a reaction flask equipped with a thermometer and a reflux condenser, the temperature was raised to 95° C. and stirred to dissolve, the temperature was lowered to 40° C., 100 g of ethylene, 40 g of vinyl acetate, 15 g of maleic anhydride, 1 g of alkenyl nitrogen phosphorus silicon monomer and 5 g of ammonium persulfate were added, the mixture was reacted at 85° C. for 3 h, the temperature was lowered to below 50° C., 0.6 g of dibutyl phthalate was added, the mixture was stirred evenly, the pH was adjusted to 5, and the modified ethylene-vinyl acetate copolymer was obtained after cooling.
[0071] (5) After 75 g of high-density polyethylene, 25 g of linear low-density polyethylene and 12 g of metallocene polyethylene are uniformly mixed, the film is blown into a film by a multi-layer co-extrusion blow molding machine, the die temperature is 200 ° C, the wind pressure is 8 MPa, the main machine frequency is 40 Hz, and the obtained film is subjected to constant temperature stretching and 45° rotary cutting to obtain a raw film; 55 g of high-density polyethylene, 20 g of linear low-density polyethylene, 5 g of modified ethylene-vinyl acetate copolymer and 10 g of mica masterbatch are prepared according to the same process to obtain an intermediate layer modified film; the intermediate layer modified film is placed between two layers of raw film and bonded with a polyurethane adhesive with a coating amount of 2 g / m 2 , winding and aging to obtain a polyethylene strong cross film.
[0072] Comparative Example 2
[0073] (1) Under a nitrogen atmosphere, 35 g of deionized water and 12 g of polyvinyl alcohol were added to a reaction flask equipped with a thermometer and a reflux condenser, the temperature was raised to 95° C. and stirred to dissolve, the temperature was lowered to 40° C., 100 g of ethylene, 40 g of vinyl acetate, 15 g of maleic anhydride and 5 g of ammonium persulfate were added, the mixture was reacted at 85° C. for 3 h, the temperature was lowered to below 50° C., 0.6 g of dibutyl phthalate was added, the mixture was stirred evenly, the pH was adjusted to 5, and the modified ethylene-vinyl acetate copolymer was obtained after cooling.
[0074] (2) After 75 g of high-density polyethylene, 25 g of linear low-density polyethylene and 12 g of metallocene polyethylene were mixed evenly, the mixture was blown into a film by a multi-layer co-extrusion blown film machine, the die temperature was 200 ° C, the wind pressure was 8 MPa, the main machine frequency was 40 Hz, and the obtained film was subjected to constant temperature stretching and 45° rotary cutting to obtain a raw film; 55 g of high-density polyethylene, 20 g of linear low-density polyethylene, 5 g of modified ethylene-vinyl acetate copolymer and 10 g of mica masterbatch were prepared according to the same process to obtain an intermediate layer modified film; the intermediate layer modified film was placed between two layers of raw film and bonded with a polyurethane adhesive with a coating amount of 2 g / m 2 , winding and aging to obtain a polyethylene strong cross film.
[0075] Comparative Example 3
[0076] 75g of high-density polyethylene, 25g of linear low-density polyethylene and 12g of metallocene polyethylene were mixed evenly and blown into film by a multi-layer co-extrusion blown film machine. The die temperature was 200°C, the wind pressure was 8MPa, and the main machine frequency was 40Hz. The obtained film was subjected to constant temperature stretching and 45° rotary cutting to obtain a raw film; 55g of high-density polyethylene, 25g of linear low-density polyethylene and 10g of mica masterbatch were prepared according to the same process to obtain an intermediate layer modified film; the intermediate layer modified film was placed between two layers of raw film and bonded with a polyurethane adhesive with a coating amount of 2g / m 2 , winding and aging to obtain a polyethylene strong cross film.
[0077] Heat resistance test: The prepared polyethylene strong cross film was made into a test sample of 100mm×50mm, and the tensile performance test was carried out at room temperature (25°C) according to method A in GB / T 328.9-2007 standard. Then the test sample was placed in an oven at 100°C for 48h, and the tensile performance test was carried out again at a stretching speed of 100mm / min.
[0078] Table 1 Heat resistance test
[0079]
[0080]
[0081] It can be seen from the test results in the above table that with the increase of the content of the modified ethylene-vinyl acetate copolymer, the tensile properties of the polyethylene strong cross film gradually increase, wherein the tensile strength at 25°C in Example 4 reaches 105.2MPa, and the mechanical properties are excellent. This is because on the one hand, the modified ethylene-vinyl acetate copolymer is similar to the polyethylene matrix structure and has good compatibility, wherein maleic anhydride can produce a bonding reaction with the hydroxyl groups on the surface of the mica masterbatch to form a cross-linked region similar to an interpenetrating network structure, so that the mica masterbatch is evenly dispersed in the matrix, significantly improving the mechanical properties of the cross film; on the other hand, the adamantane with a ring structure has a certain rigidity, so that the molecule can better transmit and disperse stress when subjected to force, reduce local stress concentration, and improve the tensile strength of the material. Comparative Example 1 and Comparative Example 2 do not contain adamantane structure, and the tensile properties are not as good as those of the embodiments; Comparative Example 3 does not contain adamantane and maleic anhydride, so that the mica masterbatch has poor dispersion performance in the matrix, is prone to agglomeration, and has poor tensile properties.
[0082] With the increase of the content of modified ethylene-vinyl acetate copolymer, the heat resistance of the polyethylene strong cross film gradually increases. After being placed at 100°C for 48 hours, the tensile strength of Example 4 is 99.8MPa, indicating that the cross film has excellent high temperature resistance. This is because when subjected to high temperature, the organic silicon in the modified ethylene-vinyl acetate copolymer will form a dense SiO2 protective layer on the surface, which can effectively prevent the external air from diffusing inward. Combined with the rigid heat-resistant structure of adamantane, the film material shows a more stable characteristic under high temperature conditions. Comparative Example 1 does not add adamantane structure, and its heat resistance needs to be further improved.
[0083] Flame retardant performance test: refer to GB / T 2406-1993 standard for limiting oxygen index test, the sample size is 140mm×5mm.
[0084] Table 2 Flame retardant performance test
[0085] Limiting oxygen index (%) Example 1 25.2 Example 2 28.6 Example 3 30.4 Example 4 32.5 Example 5 33.9 Comparative Example 1 24.8 Comparative Example 2 20.0 Comparative Example 3 19.1
[0086] It can be seen from the test results in the above table that with the increase of the content of modified ethylene-vinyl acetate copolymer, the limiting oxygen index of the polyethylene strong cross film gradually increases, among which the limiting oxygen index of implementation 5 is 33.9%, which belongs to the level of flame-retardant materials. This is because the nitrogen, phosphorus and silicon in the modified ethylene-vinyl acetate copolymer produce a synergistic flame retardant effect, among which phosphorus and silicon elements can promote the formation of the carbon layer, absorb a large amount of heat during the decomposition process, reduce the temperature of the burning polymer, and inhibit the combustion; the non-combustible gas produced by the decomposition of nitrogen can dilute the combustible gas, further improve the stability and density of the carbon layer, and the synergistic effect of the three enables the cross film to form a stronger carbon layer at high temperature, more effectively isolate oxygen and heat, and thus improve the flame retardant properties of the polyethylene strong cross film.
[0087] Low temperature flexibility and peel strength test: Tested in accordance with GB / T 23457-2009 standard
[0088] Table 3 Low temperature flexibility and peel strength test
[0089]
[0090]
[0091] In summary, those skilled in the art should understand that the present invention is not limited to the above-mentioned embodiments. The above-mentioned embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which shall fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing a polyethylene strong cross film, characterized in that: The preparation method is carried out according to the following steps: Step (1), under a nitrogen atmosphere, add deionized water and polyvinyl alcohol to a reaction flask equipped with a thermometer and a reflux condenser, heat to 85-100° C., stir and dissolve, cool to 35-45° C., add ethylene, vinyl acetate, maleic anhydride, alkenyl nitrogen phosphorus silicon adamantane monomer and ammonium persulfate, react at 80-90° C. for 2-4 hours, cool to below 50° C., add dibutyl phthalate, stir evenly, adjust the pH to 5-6, and cool to obtain a modified ethylene-vinyl acetate copolymer; Step (2), after uniformly mixing 70-85 parts of high-density polyethylene, 20-35 parts of linear low-density polyethylene and 8-15 parts of metallocene polyethylene by weight, blowing the mixture into a film by a multi-layer co-extrusion blown film machine, and subjecting the obtained film to constant temperature stretching and 45° rotary cutting to obtain a raw film; and preparing an intermediate layer modified film by the same process from 50-65 parts of high-density polyethylene, 10-25 parts of linear low-density polyethylene, 5-25 parts of modified ethylene-vinyl acetate copolymer and 10-20 parts of mica masterbatch; The modified middle layer film is placed between two layers of raw material films, and is bonded with a polyurethane adhesive, rolled up, and aged to obtain a polyethylene strong cross film.
2. The method for preparing a polyethylene strong cross film according to claim 1, characterized in that: In the step (1), the mass ratio of polyvinyl alcohol, ethylene, vinyl acetate, maleic anhydride, alkenyl nitrogen phosphorus silicon adamantane monomer, ammonium persulfate and dibutyl phthalate is 10-15:100:35-50:10-20:1-5:3-8:0.5-1.
3. The method for preparing a polyethylene strong cross film according to claim 1, characterized in that: In the step (2), the die head temperature of the multi-layer co-extrusion blown film machine is 180-220° C., the wind pressure is 5-10 MPa, and the main engine frequency is 30-50 Hz.
4. The method for preparing a polyethylene strong cross film according to claim 1, characterized in that: The preparation method of the alkenyl nitrogen phosphorus silicon adamantane monomer in step (1) is carried out according to the following steps: Step S1, under a nitrogen atmosphere, add 4-methoxyphenylphosphonic dichloride and acetonitrile to a reaction flask equipped with a thermometer, stir evenly, add adamantane and triethylamine, stir to react, concentrate under reduced pressure after the reaction is completed, purify by column chromatography, and dry to obtain phosphanidoadamantane methoxybenzene; Step S2, under a nitrogen atmosphere, add phosphanidoadamantane methoxybenzene and dichloromethane to a reaction flask equipped with a thermometer, stir evenly, dropwise add boron tribromide in an ice bath, react at 0-10° C. for 12-24 h, extract with ethyl acetate and deionized water, concentrate the organic phase, and dry to obtain phosphanidoadamantane phenol; Step S3, under a nitrogen atmosphere, add phosphanidoadamantyl phenol and N,N-dimethylformamide to a reaction flask equipped with a thermometer, stir evenly, add chlorotrivinylsilane and pyridine, stir to react, and after the reaction is completed, concentrate under reduced pressure, purify by column chromatography, and dry to obtain an olefinic nitrogen phosphanidoadamantane monomer.
5. The method for preparing the polyethylene strong cross film according to claim 4, characterized in that: In the step S1, the molar ratio of 4-methoxyphenylphosphonic dichloride, adamantane amine and triethylamine is 1:2.05-2.2:1.5-1.
8.
6. The method for preparing the polyethylene strong cross film according to claim 4, characterized in that: In step S1, the reaction temperature is 60-75° C. and the reaction time is 5-10 h.
7. The method for preparing the polyethylene strong cross film according to claim 4, characterized in that: In the step S2, the molar ratio of phosphanitrogen adamantane methoxybenzene to boron tribromide is 1:1.2-1.
5.
8. The method for preparing the polyethylene strong cross film according to claim 4, characterized in that: In the step S3, the molar ratio of phosphanitrogen adamantyl phenol, chlorotrivinylsilane and pyridine is 1:1.1-1.3:0.9-1.
05.
9. The method for preparing the polyethylene strong cross film according to claim 4, characterized in that: In step S3, the reaction temperature is 70-90° C. and the reaction time is 8-16 hours.
10. Use of the polyethylene strong cross membrane obtained by the preparation method according to any one of claims 1 to 9 in waterproof building materials.
Citation Information
Patent Citations
An exposed flame-retardant high-strength cross-laminated self-adhesive waterproof membrane and its preparation method
CN109294469B
A high-strength cross-linked polyethylene film, its preparation method, and its applications.
CN113621196B